Analysing The Essence of Fiqh Subjects In Curriculum 2013 - Fauzan Fauzan; Anis Fuadah Z (Universitas Islam Negeri Jakarta, 2017)
The essence of learning is to improve the quality of learners and to complete the national education goals that have been established, inaccordance with the mandate of the constitution. The effort to improve the quality of education through curriculum has been responded by the Ministry of Religious Affairs in 2013 on the subject of Islamic Education and Arabic Language. The implementation of the 2013 curriculum at public ElementarySchool, in this case is the subjects of Fiqh, become a break through to conductthe learning process to be more dynamic and innovative. The uses of varied methods to teach fiqh are expected to make the application of Fiqh in the dailylives of learners; both in their worship to God (‘ibādah) and social interaction(muamalah) become successful habit. DOI: 10.15408/AJIS.V17I2.6237